2005
DOI: 10.1103/physrevlett.94.045003
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the Nonlinear Regime of Raman Amplification of Ultrashort Laser Pulses

Abstract: The intensity of a subpicosecond laser pulse was amplified by a factor of up to 1000 using the Raman backscatter interaction in a 2 mm long gas jet plasma. The process of Raman amplification reached the nonlinear regime, with the intensity of the amplified pulse exceeding that of the pump pulse by more than an order of magnitude. Features unique to the nonlinear regime such as gain saturation, bandwidth broadening, and pulse shortening were observed. Simulation and theory are in qualitative agreement with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(80 citation statements)
references
References 20 publications
(21 reference statements)
2
76
0
2
Order By: Relevance
“…2). In this setup, both the amplified pulse power and the efficiency of amplification were increased by more than a factor of 4 compared to previous results [8]. This new data suggests that the improvement in efficiency is caused by the plasma density variation along the path of the pulses interaction.…”
Section: Experimental Set Upsupporting
confidence: 66%
See 2 more Smart Citations
“…2). In this setup, both the amplified pulse power and the efficiency of amplification were increased by more than a factor of 4 compared to previous results [8]. This new data suggests that the improvement in efficiency is caused by the plasma density variation along the path of the pulses interaction.…”
Section: Experimental Set Upsupporting
confidence: 66%
“…This scaling remains even if strong detuning is present [6,31] and was observed in current experiments [8,13].…”
Section: Comparison Of Experimental Data With Bra Theorymentioning
confidence: 67%
See 1 more Smart Citation
“…That is, the seed beam wavelength can be adjusted to seed SRS in a plasma which has low enough density that inverse bremsstrahlung absorption of the beam is sufficiently small for the desired plasma size. Recent experiments testing the concept for the compression of <~100 ps pump pulses to < 1ps durations have shown large amplification of short pulses can be achieved in cold laser produced plasmas [7][8][9][10] where the product of plasma wave number and Debye length (k λ D ) remains small for the brief duration of the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the backward Raman scattering (BRS) [5,6], where two light pulses and a Langmuir wave interact one another to exchange the energy, is one promising approach to create an ultra short light pulse (down to a few attoseconds [7,8]); a pulse gets compressed and intensified via this laser-plasma interaction. The BRS is successfully used to create intense pulses of the visible light frequencies [9,10]. It is natural to consider the same technique for the x-ray compression [7,8].…”
mentioning
confidence: 99%